(untitled) (Research, Society and Development, 2021)
Acute kidney injury is a reversible clinical syndrome with abrupt loss of kidney function in which there is a reduction in the glomerular filtration rate and/or oliguria. It is a serious problem in intensive care units and consequently for public health, due to the high death rate and high cost of treatment. This study aimed to analyze and describe the nursing interventions for patients with acute kidney injury in the main complications during the hemodialysis session in an intensive care unit. This is a literature review study of the narrative type and qualitative descriptive nature, extracted from scientific articles in the databases: BVS, LILACS, BIREME, SCIELO and PUBMED, Brazilian Society of Nephrology, books and Resolution of the Collegiate Board that addresses renal injury, renal replacement therapy and intensive care unit. As a result, risk factors are comorbidities, in addition to sepsis, older age, hypovolemic shock, nephrotoxicity, nodules, ischemia and prolonged hospitalization in intensive care units. It is concluded that the role of the nurse is essential and essential to identify, monitor and intervene in complications during hemodialysis. However, further studies are needed on nursing as a member of the multidisciplinary team and its importance in the care plan for these patients.